Research and practice of telecom integrated grid management based on digital transformation - Mingying ZHU; Zhuxuan HUA; Meng SHI (Dianxin kexue)
Based on the understanding of digital transformation, a scheme of digital transformation in the integrated grid management of telecom was put forward.By analyzing the overall business process of telecom, the digital transformation requirements of telecom core elements in integrated grid management were summarized, and the implementation scheme was explained in detail.Based on it, taking the specific business scenario as an example, the scheme was verified, and the practice of digital transformation was given, which provided a new idea for improving the core competitiveness of telecom in enterprise business activities.